Efektivitas Partisipasi Masyarakat dalam Musyawarah Perencanaan Pembangunan Desa (Studi Kasus di Desa Bulogading, Kecamatan Bontonompo, Kabupaten Gowa): (STUDI KASUS DI DESA BULOGADING, KECAMATAN BONTONOMPO, KABUPATEN GOWA) - Nasir, Nasir (STISIP Widyapuri Mandiri, 2026)
Community participation is an important element in realizing democratic and accountable village development planning. The Village Development Planning Conference (Musrenbangdes) is designed as a participatory forum to accommodate the aspirations of the community in determining village development priorities. However, in practice, community participation often does not run effectively. This study aims to analyze the effectiveness of community participation in Musrenbangdes in Bulogading Village, Bontonompo District, Gowa Regency, and identify the factors that affect it. This study uses a qualitative approach with a descriptive method. Data collection was carried out through observations, in-depth interviews, and documentation of village governments, Village Consultative Bodies (BPD), community leaders, and villagers. The data analysis technique uses an interactive model that includes data reduction, data presentation, and conclusion/verification. The results of the study show that community participation in Musrenbangdes has been running, but its effectiveness is still not optimal. Community participation tends to be formalistic and dominated by certain groups, while active community involvement in decision-making is still limited. Factors that affect these conditions include the level of community understanding, information disclosure, and the role of the village government in facilitating participation. This research contributes to the development of Public Administration Science, especially related to the study of community participation and village development planning, as well as providing practical recommendations for village governments in improving the quality of the implementation of Musrenbangdes.